Programa educativo aula invertida en el logro de la competencia digital en los docentes de la Institución Educativa 601582 Agustín Rivas Vásquez en el distrito de Fernando Lores 2024 - Casanova Ferreyra, Patsy Kelly (2025)
The main purpose of this research was to evaluate the effect of the educational program, flipped class, on the digital competence achievement with teachers at 601582 Agustín Rivas Vásquez school, in the district of Fernando Lores 2024. The methodology used is a quantitative approach of an experimental or intervention type, and quasi-experimental design. The study population consisted of 49 teachers, 26 in the control group and 23 in the experimental group, for data collection a written performance test of cases was used, which in turn was validated by experts. Taking into account the results, it can be affirmed that the experimental group consistently presents higher averages and lower deviations, evidencing a better performance and greater homogeneity in the variable and dimensions studied, which reflects the efficiency of the program, as well as favorable increases are observed in relation to the dimensions; in Information and digital literacy from 23.1% to 52.2%, communication and collaboration from 26.9% to 60.9%, content creation from 38.5% to 56.5%, security from 57.7% to 87% and problem solving from 61.5% to 82.6%. According to the results of the hypothesis test, the program is effective in relation to the variable and in the dimensions; information and digital literacy, communication and collaboration and security in the educational program, flipped classroom, in the development of digital competence among teachers at the educational institution 601582 Agustín Rivas Vásquez in the district of Fernando Lores-2024.